CHARACTERIZATION OF STATIONARY BLACK HOLE GEOMETRY WITH CONSTANT RICCI SCALAR - WILIARDY (NIM: 20215048), ABEDNEGO
Stationary black hole model first introduced by Kerr satisfies vacuum Einstein field equation with zero cosmological constant. As we know, our universe has non-zero cosmological constant. In this thesis, we consider a stationary black hole which satisfies non-zero cosmological constant Einstein field equation. Furthermore, the metric has an arbitrary constant Ricci scalar which imply a non-zero Einstein field equation and could be interpreted as a stationary black hole which is placed in a non-vacuum de Sitter space. Characterization of geometry is to analyze manifold singularity including physical and coordinate singularity. Moreover, we show the formed horizon and the critical limit of the black hole. Analysis of black hole thermodynamics is also performed including the calculation of surface gravity and surface area of the black hole.